Analisis Ketepatan Kode Diagnosis pada Kasus Persalinan Pasien Rawat Inap di Rumah Sakit Patria Ikkt Tahun 2022 - Angela Marsiana Siki; Deasy Rosmala Dewi; Daniel Happy Putra; Puteri Fannya (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Diagnostic coding must comply with ICD-10 rules. According to WHO, the coding of delivery cases consists of the code for the mother's condition (O00-O75), the method of delivery (O80-084), and the Outcome of delivery Z37.-., while the code is Z37.-. used as an additional code to determine the outcome of labor. So that the coder officer must have knowledge in setting the diagnosis code. Coding accuracy is very necessary because it is used as a reporting material. To determine the Standard Operating Procedure (SOP), the percentage of accuracy of the diagnosis code for inpatient labor cases based on 3M (complications, delivery method, and outcome of delivery) and the cause of the inaccuracy of the diagnosis code for labor cases. Descriptive research type with a quantitative approach. The population is medical records of inpatients in labor cases with a sample of 100 medical records. The sampling technique is by systematic random sampling. Collecting data by means of observation, interviews, and documentation. Research results: SOPs already exist, but not yet complete. The percentage of accuracy of the correct diagnosis code for labor cases is 22.33% while the incorrect diagnosis code is 77.67%. The cause of the inaccuracy of the ICD-10 code for delivery cases is that the diagnosis does not include the method of delivery and the outcome of delivery, and has never been done. evaluation or audit coding. The accuracy of the diagnosis of labor cases is still incomplete. Improve the SOP entry and complete the delivery method and outcome of delivery in medical records and registers.